Enhancing production and productivity of oilseed Brassica: research need for 21st century - PR Kumar, (Journal of Oilseed Brassica, 2026)
India is one of the largest cultivators of oilseeds cropPer capita consumption of vegetable oils hasincreased from 6.2 kg/year in 1986-87 to 14.2 kg/year during 2012-13 this eventually pushes thedemand for oil significantly.